2007
DOI: 10.1007/s11240-007-9240-5
|View full text |Cite
|
Sign up to set email alerts
|

Obtaining autotetraploids in vitro at a high frequency in Citrus sinensis

Abstract: Tetraploid plants are essential for interploid hybridization to create triploid seedless citrus.Here we report a simple and efficient in vitro method for generating autotetraploids for sweet orange (Citrus sinensis). Cell-division activity in 'Anliucheng' sweet orange callus was analyzed using flow cytometry to determine the peak frequency of cell division at which time callus in a liquid media and solid media was treated with 1000 mg l À1 colchicine. The percentage of the DNA-content-varied cells in the callu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 9 publications
1
21
0
4
Order By: Relevance
“…Cells to be treated with colchicine were harvested 7 days after the third suspension subculture. It has been found that a majority of citrus cells are in S-phase of mitotic cycle on days 6 and 7 from the beginning of their subculture (Zhang et al 2007;our observations). This phase corresponds to the stage when DNA synthesis and replication occurs and is ideal for application of colchicine since this antimitotic agent can only act on actively dividing cells (Zhang et al 2007).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Cells to be treated with colchicine were harvested 7 days after the third suspension subculture. It has been found that a majority of citrus cells are in S-phase of mitotic cycle on days 6 and 7 from the beginning of their subculture (Zhang et al 2007;our observations). This phase corresponds to the stage when DNA synthesis and replication occurs and is ideal for application of colchicine since this antimitotic agent can only act on actively dividing cells (Zhang et al 2007).…”
Section: Resultsmentioning
confidence: 96%
“…However, the frequency was low. Recently, Zhang et al (2007) described a protocol to obtain autotetraploid citrus plants using callus and generated a number of sweet orange plants.…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1930s, it has been used to increase plant ploidy levels (Blakeslee and Avery 1937). An advantage of colchicine is that it does not reduce its polyploidizing capacities after being autoclaved (Zhang et al 2007). However, in many plant species, colchicine causes side effects such as sterility, abnormal growth, chromosome losses or rearrangements and gene mutation (Luckett 1989).…”
Section: Antimitotic Agents Used In In Vitro Chromosome Doublingmentioning
confidence: 99%
“…It contributes to the effect and toxicity of the treatment. In many studies, antimitotic agents are dissolved in DMSO (Allum et al 2007;Awoleye et al 1994;Greplova et al 2009;Hamill et al 1992;Kermani et al 2003;Khosravi et al 2008;Stanys et al 2006;Subrahmanyam and Kasha 1975;Takamura et al 2002;Väinölä 2000;Yang et al 2006;Zhang et al 2007Zhang et al , 2010a. DMSO increases cell permeability and allows increased absorption of chemicals (Hamill et al 1992).…”
Section: Concentration and Exposure Timementioning
confidence: 99%
“…Marie & Brown (1993) propuseram coefi cientes de variação de 1 a 2%, para resultados de Paralelamente aos estudos realizados para a defi nição de um método seguro para a propagação in vitro de genótipos elite de híbridos entre capim-elefante e milheto, a Embrapa Gado de Leite tem trabalhado para a obtenção de materiais hexaploides por meio da duplicação cromossômica de híbridos triploides (Abreu et al, 2006;Barbosa et al, 2007). Como as estratégias adotadas para duplicação cromossômica geralmente utilizam protocolos de exposição de explantes in vitro a agentes antimitóticos (Gu et al, 2005;Yang et al, 2006;Zhang et al, 2007), a obtenção de protocolos de embriogênese somática, para híbridos triploides de capim-elefante e milheto, além de representar uma possibilidade de multiplicação de genótipos elite, representa uma alternativa para indução in vitro de duplicação cromossômica, que visa à obtenção de híbridos hexaploides férteis.…”
Section: Resultsunclassified